If
where are integers independent of . Evaluate: .
Details and Assumptions :
denotes derivative of
The greatest common divisor between and is 1/
is square free.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let ω , ω 2 denote the complex cube roots of unity such that
ω = 2 − 1 + i 3
ω 2 = 2 − 1 − i 3
Therefore
f ( x ) = ( x + ω ) ( x + ω 2 ) 1 = ω 2 − ω 1 ( x + ω 1 − x + ω 2 1 ) .
We know that the n t h derivative of x 1 is x n + 1 ( − 1 ) n n !
Therefore, we can write
f 6 ( x ) = ω 2 − ω 6 ! ( ( x + ω ) 7 1 − ( x + ω 2 ) 7 1 ) = ω 2 − ω 6 ! ( ( x + ω ) 7 ( x + ω 2 ) 7 ( x + ω 2 ) 7 − ( x + ω ) 7 )
x + ω 2 = ( x − 2 1 ) + i ( − 2 3 ) = r ( c o s θ − i s i n θ ) ... ( 1 )
x + ω = ( x − 2 1 ) + i ( 2 3 ) = r ( c o s θ + i s i n θ ) .... ( 2 )
Therefore,
( x + ω 2 ) 7 = r 7 ( c o s 7 θ − i s i n 7 θ ) ...... ( 3 )
( x + ω ) 7 = r 7 ( c o s 7 θ + i s i n 7 θ ) ......... ( 4 )
ω 2 − ω = − i 3 ............................... ( 5 )
Therefore from equations ( 3 ) , ( 4 ) and ( 5 ) we can write,
f 6 ( x ) = − i 3 6 ! ( r 1 4 r 7 ( − 2 i s i n 7 θ ) ) = 3 6 ! r 7 2 s i n 7 θ
Now multiplying and dividing by s i n 7 θ we get,
f 6 ( x ) = 3 ( 6 ! ) ( 2 ) ( r s i n θ ) 7 s i n 7 θ × s i n 7 θ ...... ( 6 )
From equations ( 1 ) and ( 2 ) we can write
( x + ω ) − ( x + ω 2 ) = 2 r i s i n θ
ω − ω 2 = 2 r i s i n θ
( 2 3 ) 7 = ( r s i n θ ) 7
Now substituting value of ( r s i n θ ) 7 from above in equation ( 6 ) we get,
f 6 ( x ) = ( 3 ) 8 ( 6 ! ) ( 2 ) 8 ( s i n 7 θ ) ( s i n 7 θ )
But from equation ( 1 ) (or even ( 2 ) ) we can write θ = a r c t a n ( 2 x − 1 3 )
hence,
f 6 ( x ) = 9 2 0 4 8 0 sin 7 ( arctan ( 2 x − 1 3 ) ) sin ( 7 ⋅ arctan ( 2 x − 1 3 ) )